Quantitative analysis of gene expression changes in response to genotoxic compounds. (March 2017) - Morris, Ceri A.; El-Hiti, Gamal A.; Weeks, Ian; Woodhead, Stuart; Smith, Keith; Kille, Peter
Abstract: Techniques that quantify molecular endpoints sufficiently sensitive to identify and classify potentially toxic compounds have wide potential for high-throughput in vitro screening. Expression of three genes, RAD51C, TP53 and cystatin A ( CSTA ), in HEPG2 cells was measured by Q-PCR amplification. In parallel, we developed alternative assays for the same 3 gene signature based on an acridinium-ester chemiluminescent reporter molecule. HEPG2 cells were challenged with eighteen different compounds ( n = 18) chosen to represent compounds that are genotoxic ( n = 8), non-genotoxic non-carcinogenic ( n = 2) or have a less well defined mechanism of action with respect to genotoxicity ( n = 8). At least one of the three genes displayed dysregulated expression in the majority of compounds tested by Q-PCR and ten compounds changed the CSTA expression significantly. Acridinium-ester labelled probes for the three genes were synthesised and tested. Analytical sensitivity was characterised and suggested a limit of detection generally better than 0.1 fmol but often 10–50 attomol. A linear amplification step was optimised and this quantitative method detected statistically significant increases in RAD51C and CSTA expression in agreement with the Q-PCR results, demonstrating the potential of this technology. The broad agreement of the amplified chemiluminescent method and Q-PCR in measuring gene expression suggests wider potential application for this chemiluminescent technology. Highlights: Development of in vitro assays to measure 3 genes ( RAD51C, CSTA, TP53) . Expression profiles in response to exposure of HEPG2 cells to 18 compounds CSTA dysregulation was the most effective indicator of exposure. Optimisation of a novel method for chemiluminescent detection of nucleic acid targets New format is capable of detecting gene expression levels in cell lines.